"Thematic concern" analysis in the process of developing cost management skills curriculum - Amir Hussin, Muhammad Rosni; Ismail, Kamariah; Alias, Rose Alinda (2015)
Although the Malaysian government has already provided various entrepreneurial training programmes, Malaysian SME owner managers still lack entrepreneurial skills.Among the important skills that are still lacking are cost management skills.Thus, the current research attempts to develop cost management skills curriculum using action research approach.Action research approach is a cyclical process of planning, acting, observing and reflecting.According to several studies, the planning stage is the most critical stage of the action research cycle. At the planning stage or “thematic concern” stage, the problem or situation that needs to be improved must be clearly analysed.Hence, this paper discusses in detail the “thematic concern" analysis in developing cost management skills curriculum for SME training programmes in Malaysia.This paper triangulates various data sources, such as interviews and other secondary data. Among the important findings of this paper are SME owner managers in Malaysia still lack cost management skills knowledge.Furthermore, entrepreneurial training programmes also lack curriculum related to cost management skills.